KEMAMPUAN MENGANALISIS NILAI SOSIAL DALAM NASKAH DRAMA REMAJA SIMPHONY ANAK JALANAN KARYA IGN ARYA SANJAYA OLEH SISWA KELAS XI SMA NEGERI 3 KUTACANE TAHUN PEMBELAJARAN 2021/2022 - Mita Purnama Sari; James Marudut; Lusi Selvia Fitri (STKIP USMAN SAFRI KUTACANE, 2022)
Mita Purnama Sari 15317001017 This thesis is entitled: Ability to Analyze Social Values ​​in Street Children Symphony Drama Scripts by Ign Arya Sanjaya By class XI students of SMA N 3 Kutacane in the academic year 2021/2022. This study aims to obtain an overview of the Ability to Analyze Social Values ​​in Street Children Symphony Drama Scripts by Ign Arya Sanjaya by class XI students of SMA N 3 Kutacane in the academic year 2021/2022. The population in this study were all class XI students of SMA Negeri 3 Kutacane. which amounted to 103 students. From the population, the sample was determined by purposive sampling. The sample in this study amounted to 29 students who were taken using purposive sampling. Based on the theoretical framework, the hypothesis in this study is that there is an ability to analyze social values ​​in street children's Symphony Drama Scripts by Ign Arya Sanjaya by class XI students of SMA N 3 Kutacane in the 2021/2022 academic year. This is evident from the average value of the student's initial test with a standard deviation of Rp. Based on the data from the results of the student's initial and final tests and if it is associated with the KKM value of the Indonesian language subject of 75, after tcount = 44, it is obtained then consulted with the ttable value at a significant level of 5% with dk = N - 1 = 29 - 1 = 28 , then the value of ttable = 2.04841. So, the value of tcount > t table or 44 > 2,04841, the hypothesis is accepted.